Tensões, deformações e deslocamentos em estruturas de concreto armado e protendido. - Machado, Claudinei Pinheiro (1990)
The present work focuses the behaviour of reinforced an prestressed concrete linear structures through time (with extension to slabs). One of its purposes is to study general cross sections, fully cracked or not and which are subjected to bending or combined axial and bending loads due to service loads where bending and axial loads are or could be considered constant i relation to time. It is developed a single formulation for both prestressed and reinforced concrete so as to save as a working tool to the development of more elaborated solut ions, keeping in ( fully cracked) . Attention is given to the study of some methods for the determination of stresses, deformations and displacements of structures which are considered by the author the most relevant nowadays: Ghali-Favre; Debernardi; CEB. It is shown that in more rigorous methods the solut ions are generally obtained by means of relatively complex systems of equations, which require laborious iterative solution, as in the P.G. Debernardi Method, which is studied here in detail. In order to make analysis of normal cross sections easier by this method it is proposed a derect alternative solution. Less panistaking methods with minor accuracy are also considered, though the results are yet satisfactory. Their advantage is to give answer in a shorter time, as in the case of the CEB Method. In almost all methods studied here, the solution of the Hereditary Integral Equation (the Volterra Integral type) has been obtained by the use of the Age Adjusted Effective Modulus Method.